The Study of The Architectural Characteristics of Rumah Godong of The Anak Dalam Tribe in Sumatra - Muhammar Khamdevi (Prodi Arsitektur Universitas Matana, 2021)
The Anak Dalam tribe (Suku Anak Dalam or Suku Kubu or Orang Rimba) is one of the tribes in Central Sumatra. This tribe still lives simply and depends on nature in the forest. This tribe has its own very simple traditional house, which indicates the earliest vernacular houses in Sumatra, especially in the